Evaluation of the efficacy of manual toothbrushes in reducing bacterial biofilm in interdental spaces – comparative analysis - Chałas, Renata; Maksymiuk, Paweł; Piątek, Dominika; Bieżanek, Tomasz; Sobieszczański, Jarosław (Journal of Stomatology, 2015)
Introduction. Proper oral hygiene is essential to maintain oral health and aesthetic appearance. Basic care involves daily tooth brushing. An appropriate toothbrush should be adapted to the patient’s oral health, periodontal status, age and habits. There is a wide range of toothbrushes available on the market, so indicating those that best remove plaque should be beneficial for the patients. Aim of the study. To evaluate the effect of introducing new toothbrushes with different types of bristles to daily oral hygiene for the purpose of efficient removal of dental plaque from interdental spaces. Material and methods. The study comprised thirty volunteers in whom measurement of the oral hygiene was performed twice with the API index – at baseline (T0 – API 1) and after two weeks (T1 – API 2). Patients after the first measurement of the index were randomly divided into three groups, each including ten subjects. Patients in each group received one of the three types of toothbrushes: Colgate 360° Surround medium, Colgate Premier Clean medium, Curaprox 3960 super soft, and standard toothpaste containing 1450 ppm fluoride. A clinical study was supplemented with a survey on hygiene habits. Results. The majority of respondents (76.7%) declared regular tooth brushing twice a day. Among the respondents, most people (60%) reported the use of manual toothbrushes with soft bristles, 23.3% of respondents indicated a manual toothbrush with a medium-soft bristle, while 20% reported the use of electric toothbrushes. Almost all study participants (96.7%) used toothpaste with fluoride. The average score of the API specified before introduction of a new toothbrush in the group was 50.36 and afterwards 36.40. Average reduction in the API value was 13.96. The greatest improvement in reducing biofilm formation, as measured by the API index, was recorded in Group 1 – 21.60, and the lowest in Group 3 – 3.60. Conclusions. Introduction of a new toothbrush can contribute to better removal of plaque from interdental spaces. The length and arrangement of bristles in the cleaning part of the toothbrush may have an impact on the efficacy of removing dental plaque from approximal areas.